O ensino de projeto de produtos e design com a utilização de protótipos computacionais como artefato educacional - Souza, Adriano José Sorbile de (2021)
This work has the general objective of proposing a model that helps the teacher to design an educational artifact with the properties and specific characteristics of product design, present the idea of learning using an educational artifact that in the case of product development will be a 3D prototype and provide flexibility in terms of adjustment, modifications and settings contributing to assist in the teaching learning process. The research method is exploratory and comprises the teaching process of product design and educational approaches. A bibliographical survey is carried out about design methodologies applied to the development of product design in the pre-development, development and post-development stages observing the characteristics and design requirements that have been developed in the curricula for technical and higher education in Product Design and Industrial Production Management courses. An approach is made about the problems present in the teaching of product design taking into consideration the motivation in the school environment and behavioral and constructivist learning, as well as the preparation of the master to assume the pedagogical role in higher education, taking into consideration the classification of different goals and abilities that educators define for their students through Bloom's taxonomy and Dreyfus' skill acquisition, assuming that the longer one practices following rules and procedures, the learner becomes more experienced and more competent in a job or task. The educational artifact is based on the Design Science concepts that focus on the creation of artifacts, that is, something that was built by man with the goal of improving the efficiency of organizations, people's living conditions, among others. Design Science aims to create artifacts to build new realities and new knowledge. The proposed model is based on the educational data collected, exemplifying the use of the model from three-dimensional computer prototypes as an educational artifact, helping the teacher in the learning process and indicates that in future work the model can be applied in the classroom with the objective of verifying if the results in the teaching-learning process were achieved statistically